Polyamine oxidase 5 loss‐of‐function mutations in Arabidopsis thaliana trigger metabolic and transcriptional reprogramming and promote salt stress tolerance. (13th April 2016) - Zarza, Xavier; Atanasov, Kostadin E.; Marco, Francisco; Arbona, Vicent; Carrasco, Pedro; Kopka, Joachim; Fotopoulos, Vasileios; Munnik, Teun; Gómez‐Cadenas, Aurelio; Tiburcio, Antonio F.; Alcázar, Rubén
Abstract: The family of polyamine oxidases (PAO) in Arabidopsis ( AtPAO1–5 ) mediates polyamine (PA) back‐conversion, which reverses the PA biosynthetic pathway from spermine and its structural isomer thermospermine (tSpm) into spermidine and then putrescine. Here, we have studied the involvement of PA back‐conversion in Arabidopsis salinity tolerance. AtPAO5 is the Arabidopsis PAO gene member most transcriptionally induced by salt stress. Two independent loss‐of‐function mutants ( atpao5‐2 and atpao5‐3 ) were found to exhibit constitutively higher tSpm levels, with associated increased salt tolerance. Using global transcriptional and metabolomic analyses, the underlying mechanisms were studied. Stimulation of abscisic acid and jasmonate (JA) biosynthesis and accumulation of important compatible solutes, such as sugars, polyols and proline, as well as TCA cycle intermediates were observed in atpao5 mutants under salt stress. Expression analyses indicate that tSpm modulates the transcript levels of several target genes, including many involved in the biosynthesis and signalling of JA, some of which are already known to promote salinity tolerance. Transcriptional modulation by tSpm is isomer‐dependent, thus demonstrating the specificity of this response. Overall, we conclude that tSpm triggers metabolic and transcriptional reprogramming that promotes salt stress tolerance in Arabidopsis . Abstract : Arabidopsis atpao5 loss‐of‐function mutants exhibit constitutive accumulation of thermospermine (tSpm) that associates with enhanced salt tolerance. tSpm triggers transcriptional and metabolic changes that involve promotion of ABA and JA pathways, accumulation of TCA cycle intermediates, compatible solutes along with other effects that additively contribute to salt tolerance. We provide evidence for the involvement of tSpm in plant abiotic stress tolerance.